Congenital double lower lip: report of a case - M. M. CHIDZONGA & L. MAHOMVA (Paediatric Dentistry, 2006)
A case of the management of a congenital double lower lip in a 2-week-old female child: is described. The mother stated that the child was having difficulties when suckling and was also worried about the unsightly appearance.